Agenda Ambiental da Administração Pública (A3P): estudo da gestão ambiental no IFSP, baseado nas diretrizes estabelecidas pela A3P - Biscegli, Adriana Margarida de Jesus (Universidade Federal de São Carlos, 2025)
The search for sustainability has become an essential condition for the preservation of life. Climate change and natural disasters have increasingly highlighted the urgency of balancing development and environmental conservation, which has led the Brazilian government to expand its legal framework and invest in programs aimed at raising awareness and mitigating adverse impacts.The Environmental Agenda in Public Administration (A3P) is a program created by the Ministry of the Environment, which aims to encourage public agencies in the country to implement sustainability practices. Considering the importance of Higher Education Institutions (HEIs) in the production and dissemination of knowledge, as well as their social influence, this research aims to investigate the theme of environmental management on the campuses of the Federal Institute of São Paulo (IFSP), conducting an analysis of the sustainable actions implemented on the different campuses of the institution based on the axs that make up the Environmental Agenda in Public Administration (A3P). The research is classified as exploratory and descriptive, with a quantitative approach, outlined as a survey, of an applied nature. Data collection was conducted thru the application of a questionnaire and supplemented by documentary research and the gathering of information from the IFSP campuses' websites. The research results indicate that the IFSP campuses that participated in the study partially comply with the guidelines proposed by the Environmental Agenda in Public Administration. However, some challenges need to be faced, especially regarding the consolidation and awareness of sustainability committees, as well as the adoption, in the different campuses of the institution, of the actions and events of good environmental practices proposed by the IFSP Sustainability Plan.
Environmental Agenda Of Public Administration (A3P): study of environmental management at IFSP, based on the guidelines established by A3P
Keywords: Agenda Ambiental da Administração Pública (A3P); Sustentabilidade; Gestão Ambiental; Instituições de Ensino Superior (IES); Instituto Federal de São Paulo (IFSP); Environmental Agenda of Public Administration (A3P); Sustainability; Environmental Management; Higher Education Institutions (IES); Federal Institute of São Paulo (IFSP); CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; 13. Ação contra a Mudança Global do Clima